Speed Sensorless Fault-Tolerant Drive System of 3-Phase Induction Motor Using Switching Extended Kalman Filter - M. Jannati; N. R. N. Idris; M. J. A. Aziz (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Speed sensorless vector control of 3-phase induction motor under open-phase fault (faulty 3-phase induction motor) ased on Indirect Rotor Field-Oriented Control (RFOC) is proposed in this paper. To ensure high performance FOC of induction motor drives, the estimation of the rotor speed is necessary. However, the algorithm used to estimate the rotor speed for a 3-phase induction motor cannot be used directly for a faulty 3-phase induction motor. This is because the faulty induction motor model is different from the healthy 3-phase induction motor. To overcome this problem, in this paper a new switching Extended Kalman Filter (EKF) s proposed to update online the rotor speed. The proposed algorithm can be used for estimation of rotor speed in both healthy and faulty conditions. MATLAB simulation results are carried out to show the capability of the proposed drive system. The results show the activity of the proposed method at wide range speed operation.